2002
DOI: 10.1042/bj3630321
|View full text |Cite
|
Sign up to set email alerts
|

Copper supplementation restores cytochrome c oxidase activity in cultured cells from patients with SCO2 mutations

Abstract: Human SCO2 is a nuclear-encoded Cu-binding protein, presumed to be responsible for the insertion of Cu into the mitochondrial cytochrome c oxidase (COX) holoenzyme. Mutations in SCO2 are associated with cardioencephalomyopathy and COX deficiency. Studies in yeast and bacteria have shown that Cu supplementation can restore COX activity in cells harbouring mutations in genes involving Cu transport. Therefore we investigated whether Cu supplementation could restore COX activity in cultured cells from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The EPI-743 treatment was beneficial to patients with LS due to mutations in SURF1 and in LS with secondary COX deficiency due to mutated ETHE1. 17 In vitro studies in patient fibroblasts showed that copper 18 and copper with bezafibrate supplementation rescued cells harboring mutations in SCO2 encoding a COX copper-chaperone 19 while L-cystein supplementation improved mitochondrial function in cells with TRMU mutations. 20 However, as the COX6B1 defect does not cause LS and the protein is not a copper chaperone but an integral COX subunit, we evaluated a number of other potentially beneficial molecules for their ability to improve mitochondrial function in the patient's fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The EPI-743 treatment was beneficial to patients with LS due to mutations in SURF1 and in LS with secondary COX deficiency due to mutated ETHE1. 17 In vitro studies in patient fibroblasts showed that copper 18 and copper with bezafibrate supplementation rescued cells harboring mutations in SCO2 encoding a COX copper-chaperone 19 while L-cystein supplementation improved mitochondrial function in cells with TRMU mutations. 20 However, as the COX6B1 defect does not cause LS and the protein is not a copper chaperone but an integral COX subunit, we evaluated a number of other potentially beneficial molecules for their ability to improve mitochondrial function in the patient's fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemistry-For histochemical staining of cytochrome c oxidase activity (35), cells grown on glass coverslips were airdried for 1 h at room temperature and then preincubated with 1 mM CoCl 2 in 50 mM Tris-HCl, pH 7.6, containing 10% sucrose for 15 min at room temperature. After rinsing with 0.1 M sodium phosphate, pH 7.6, containing 10% sucrose, the cells were incubated for 6 h at 37°C in incubation medium (10 mg of cytochrome c, 10 mg 3,3Ј-diaminobenzidine hydrochloride, 2 mg of catalase, 10% sucrose in 0.1 M sodium phosphate, pH 7.6).…”
Section: Methodsmentioning
confidence: 99%
“…Subfragments of each coactivator denoted as A, B, C, or D with their amino acid coordinates shown in parentheses were used in S-tag pulldown assays with 35 S-labeled transcription factor. Binding of the various subfragments to each 35 S-radiolabeled factor was compared with that of S-tagged thioredoxin (Trdx) as a negative control. Bound proteins were eluted from the S-protein-agarose and visualized by autoradiography.…”
Section: Similarities and Differences In Transcription Factormentioning
confidence: 99%
“…Histochemistry. Histochemical staining for cytochrome c oxidase (COX) activity was done as described (20). Briefly, cells grown on glass coverslips were air-dried for 1 h at room temperature and preincubated with 1 mmol/L CoCl 2 and 50 AL of DMSO in 50 mmol/L Tris-HCl (pH 7.6), containing 10% sucrose, for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%